2019
DOI: 10.1111/padm.12571
|View full text |Cite
|
Sign up to set email alerts
|

How empowering leadership reduces employee silence in public organizations

Abstract: The intentional withholding of critical work-related information can have serious negative consequences in public organizations. Yet, few studies have examined why public employees intentionally remain silent about problems and how to prevent such behaviour.This article provides insights into how managers may lower employee silence in government organizations. We develop a model that suggests that empowering leadership by frontline supervisors reduces public employee silence, by improving employee trust in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 65 publications
2
36
0
1
Order By: Relevance
“…In addition, coworker trust was included as a boundary condition for the relationship between silence and stress to examine whether it can alleviate the effects of silence on stress. Trust has been found to be significantly related to silence (e.g., Dedahanov & Rhee, 2015; Hassan et al., 2019; Nikolaou et al., 2011). Trust towards coworkers involves positive expectations and confidence in terms of one’s fellow members’ ability, integrity, and benevolence (Mayer et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coworker trust was included as a boundary condition for the relationship between silence and stress to examine whether it can alleviate the effects of silence on stress. Trust has been found to be significantly related to silence (e.g., Dedahanov & Rhee, 2015; Hassan et al., 2019; Nikolaou et al., 2011). Trust towards coworkers involves positive expectations and confidence in terms of one’s fellow members’ ability, integrity, and benevolence (Mayer et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Park & Hassan, 2018). Although the role of leadership in empowering public employees has not yet been fully studied, some studies have suggested that positive intervention by managers symbolizing delegation of authority and display of trust in followers improves the work attitude of employees (Amundsen & Martinsen, 2015;Hassan et al, 2019;M. Kim et al, 2018).…”
Section: Leadership and Performancementioning
confidence: 99%
“…Similarly, while the existence of a hierarchy is a precondition for supervisors to have this psychological reaction to their place in it, this psychological mechanism is distinct from the existence of the hierarchy itself; all organizations have hierarchies, but not all organizations exhibit widespread resistance of supervisors to employee voice. Although the psychology of leaders' openness to employee voice is widely studied in private sector management (Ashford et al, 2009;See, Morrison, Rothman, & Soll, 2011), there has been little attention to it in the public sector context, with Hassan et al (2019) as a recent exception.…”
Section: Voice and Hierarchymentioning
confidence: 99%
“…Although public innovation is typically understood to take a range of forms, including new services or contractual forms (Walker, 2008), we focus more narrowly on work process reforms. Our focus on lower-and middle-level bureaucrats contributes to the small body of studies on "bottom-up" innovation and voice (Fernandez & Moldogaziev, 2012;Hassan, 2015;Hassan, DeHart-Davis, & Jiang, 2019) and on the determinants and consequences of bureaucrats' sense of control over their work, as represented within this special issue by Honig (2020) and Kay, Rogger, and Sen (2020). A deeper understanding of innovation and voice by rank-and-file bureaucrats in the literature seems especially important as Moldogaziev and Resh (2016) find that these internally driven ideas are perceived to be more successful than those imposed top-down or by external actors.…”
Section: Introductionmentioning
confidence: 99%